KAJIAN SOSIO-TEOLOGIS TERHADAP MAKNA METAFORA DALAM NATONI PADA PENERIMAAN PENDETA DI GMIT - Akwila Priska Ibu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
Natoni is one of the traditions, exactly a traditional speech, to Meto tribe. As a tradition, natoni is often used in ceremonial activities by the Meto tribe in Timor Island. As an expression closely related to the gods, natoni is considered very sacred to the Meto tribe. The ceremony used is, among others, a reception where natoni is the sense of respect and appreciation to others. This study was conducted to describe and to analyze the knowledge the congregation in Timor has about the meaning of metaphors in natoni of the reception of pastors at GMIT. A qualitative research method with a descriptive approach was used in this study and in-depth interview was used as technique of collecting data. The result shows that the congregation in Timor understands, interprets, and uses metaphors or descriptive language in the natoni of acceptance of the priests as respect and hope for the priests in which the metaphor is obtained from the lives of Meto tribe ancestors. In addition, the congregation’s understanding of the metaphor is currently based on the illustration of story in the Bible. Thus, the understanding is manifested into natoni verses with metaphors.